Organic Residue Amendments to Modulate Greenhouse Gas Emissions From Agricultural Soils - Brenzinger, Kristof; Drost, Sytske M.; Korthals, Gerard; Bodelier, Paul L. E. (Frontiers in Microbiology, 2018)
Organic fertilizers have been shown to stimulate CH4 uptake from agricultural soils. Managing fertilizer application to maximize this effect and to minimize emission of other greenhouse gasses offers possibilities to increase sustainability of agriculture. To tackle this challenge, we incubated an agricultural soil with different organic amendments (compost, sewage sludge, digestate, cover crop residues mixture), either as single application or in a mixture and subjected it to different soil moisture concentrations using different amounts of organic amendments. GHG fluxes and in vitro CH4 oxidation rates were measured repeatedly, while changes in organic matter and abundance of GHG relevant microbial groups (nitrifiers, denitrifiers, methanotrophs, methanogens) were measured at the end of the incubation. Overall the dynamics of the analysed GHGs differed significantly. While CO2 and N2O differed considerably between the treatments, CH4 fluxes remained stable. In contrast, in vitro CH4 oxidation showed a clear increase for all amendments over time. CO2 fluxes were mostly dependent on the amount of organic residue that was used, while N2O fluxes were affected more by soil moisture. Several combinations of amendments led to reductions of CO2, CH4 and/or N2O emissions compared to un-amended soil. Most optimal GHG balance was obtained by compost amendments, which resulted in a similar overall GHG balance as compared to the un-amended soil. However, compost is not very nutrient rich potentially leading to lower crop yield when applied as single fertilizer. Hence, the combination of compost with one of the more nutrient rich organic amendments (sewage sludge, digestate) provides a trade-off between maintaining crop yield and minimizing GHG emissions. Additionally, we could observe a strong increase in microbial communities involved in GHG consumption in all amendments, with the strongest increase associated with cover crop residue mixtures. Future research should focus on the interrelation of plants, soil and microbes and their impact on the global warming potential in relation to applied organic amendments.